Bagaimana Informasi Mendorong Pembelian: Peran Mediasi Adopsi Informasi di Sektor Kuliner - Shafa' Annisa Puspasari; Patmi Rahayu, Wening; Churiyah, Madziatul (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how information adoption mediates the influence of information usefulness, information diagnosticity, and subjective norms on purchase decisions in the culinary sector. A quantitative approach and purposive sampling were applied, with 230 respondents. Data were analyzed using SEM-PLS. Results indicate that the three variables significantly affect both information adoption and purchase decisions. Information adoption partially mediates these relationships. The findings offer insights for culinary businesses to enhance consumer engagement through social media content that is credible, relevant, and socially endorsed.